Out Of Pocket Expenditure Of End Stage Renal Disease Patients For Maintenance Haemodialysis. - Asaduzzaman , Md; Islam, Shafiqul; Haque, Md Emdadul; Patwary, Md Helal Morshed (Bangladesh Armed Forces Medical Journal, 2024)
Background: End stage renal disease (ESRD) is a major and growing public health problem in Bangladesh. It is linked to higher hospitalization rates, lost productivity, illness, and early death, and it is a major cost on people, health care systems, and societies. Haemodialysis as a life saving measure can save patients but out-of-pocket expenditure of Haemodialysis in Bangladesh is high in comparison to their monthly family income. Therefore, it places a significant financial strain on the families of the disease victims. The aim of this study was to find out the out-of-pocket expenditure of ESRD patients for maintenance haemodialysis. Methods: This descriptive cross sectional study was carried out among 160 ESRD patients getting haemodialysis at Dialysis centre of a selected tertiary government hospital in Dhaka during the period of January to December 2022. Simple random sampling technique was followed. Data were collected by face to face interview with a semi-structured questionnaire and by check list reviewing medical documents. Results: The mean (±SD) age of the respondents was 49.28 ±12.706 years. Majority (60.6%) were male and 39.4% were female. Majority (29.4%) had secondary followed by 21.9% who had higher secondary level of education. About three fourths (71.9%) were from urban, 18.8% from rural, 8.1% from semi-urban areas and 1.3% were slum dwellers. The median of monthly family income was Tk. 20000 (interquartile range 15750). The median (IQR) total direct cost was Tk. 15983 (7203). The mean (±SD) total indirect cost was Tk. 5431.25±1128.17. The mean (±SD) total haemodialysis cost was Tk. 24205.59 ±17164.580. Conclusion: Out-of-pocket expenditure of Haemodialysis in Bangladesh is high in comparison to monthly family income and it poses huge financial burden to the families of the victims of end stage renal disease. The study recommended cost effective measures like subsidized or free of cost treatment of ESRD and free of cost haemodialysis of patients to reduce the financial burden of the families. Bangladesh Armed Forces Med J Vol 56 No (1) June 2023, pp 28-34